Thermal enhancement strategies for fluid jets impinging on a heated surface - King, Andrew (Curtin University, 2007)
This research investigation examines the thermal behaviour of single and arrays of fluid jets impinging at heated surfaces, and formulates enhancement schemes for the jet impingement heat transfer processes for high-intensity cooling applications. The proposed techniques are numerically modelled and analysed over a wide parametric range to identify flow characteristics leading to thermal enhancement and optimum performance. The first scheme applies to a single fluid jet and incorporates a protruding object at the impingement surface to improve heat transfer. In this, a conical protrusion of high thermal conductivity is attached to the heated surface directly beneath the jet. Three different aspect ratios of 0.5, 1 and 2 are investigated for the protrusion while the inclusion of a fillet at the base of the cone is also studied. Jet Reynolds numbers between 100 and 30,000 are modelled. The observed thermal performance is compared with a reference case having no surface attachment. With this arrangement, the heat transfer rate typically varies between 10 and 40 percent above the reference case although depending on certain parametric combinations, the heat transfer may increase above or decrease below the reference performance. The highest indicated increase in heat transfer is about 90 percent while 15 percent below is the lowest. Careful selection of cone surface profile creates potential for further thermal enhancement.The second scheme applies to a single fluid jet and incorporates a recess in the impingement surface to improve heat transfer. In this, a cylindrical cavity is introduced to the surface beneath the jet into which the fluid jet impinges. The effects of the cavity on heat transfer are examined for a number of different cavity diameters, cavity depths and jet discharge heights wherein a surface without a cavity is taken as the reference surface. Cavity diameters of 2, 3 and 4 times the jet diameter are investigated at cavity depths between zero and 4 times the jet diameter. Jet discharge heights range between 2 jet diameters above the reference surface to 2 jet diameters below the reference surface. The jet Reynolds number is varied between 100 and 30,000. With this enhancement technique, increases in heat transfer rates of up to 45 percent are observed when compared to the reference performance. The thermal performance of fluid jet arrays is examined by altering square or hexagonal array configurations to identify flow characteristics leading to optimal heat transfer rates. For this, the jet to jet spacing is varied between 1.5 and 7 times the jet diameter while the jet to surface height is varied between 2 and 6 times the jet diameter. Jet Reynolds numbers between 100 and 30,000 are investigated. For each configuration, a critical jet-to-jet spacing is identified below which the heat transfer is observed to reduce significantly. Correlations for the expected heat transfer for a square or hexagonal array are presented in terms of the jet to jet spacing, jet height and jet Reynolds number.